Long-term outcomes after out-of-hospital cardiac arrest in relation to socioeconomic status. (October 2021) - Møller, Sidsel; Wissenberg, Mads; Søndergaard, Kathrine; Kragholm, Kristian; Folke, Fredrik; Hansen, Carolina Malta; Ringgren, Kristian B.; Andersen, Julie; Lippert, Freddy; Møller, Amalie Lykkemark; Køber, Lars; Gerds, Thomas Alexander; et al.
Abstract: Aims: This study aimed to examine whether socioeconomic differences exist in long-term outcomes after out-of-hospital cardiac arrest (OHCA). Methods: We included 2309 30-day OHCA survivors ≥ 30 years of age from the Danish Cardiac Arrest Registry, 2001–2014, divided in tertiles of household income (low, medium, high). Absolute probabilities were estimated using logistic regression for 1-year outcomes and cause-specific Cox regression for 5-year outcomes. Differences between income-groups were standardized with respect to age, sex, education and comorbidities. Results: High-income compared to low-income patients had highest 1-year (96.4% vs. 84.2%) and 5-year (87.6% vs. 64.1%) survival, and lowest 1-year (11.3% vs. 7.4%) and 5-year (13.7% vs. 8.6%) risk of anoxic brain damage/nursing home admission. The corresponding standardized probability differences were 8.2% (95%CI 4.7–11.6%) and 13.9% (95%CI 8.2–19.7%) for 1- and 5-year survival, respectively; and −4.5% (95%CI −8.2 to −1.2%) and −5.1% (95%CI −9.3 to −0.9%) for 1- and 5-year risk of anoxic brain damage/nursing home admission, respectively. Among 831 patients < 66 years working prior to OHCA, 72.1% returned to work within 1 year and 80.8% within 5 years. High-income compared to low-income patients had the highest chance of 1-year (76.4% vs. 58.8%) and 5-year (85.3% vs. 70.6%) return to work with the corresponding absolute probability difference of 18.0% (95%CI 3.8–32.7%) for 1-year and 9.4% (95%CI −3.4 to 22.3%) for 5-year. Conclusion: Patients of high socioeconomic status had higher probability of long-term survival and return to work, and lower risk of anoxic brain damage/nursing home admission after OHCA compared to patients of low socioeconomic status.